Definition, assessment and treatment of cognitive impairment associated with schizophrenia: expert opinion and practical recommendations - Vita, Antonio; Barlati, Stefano; Cavallaro, Roberto; Mucci, Armida; Riva, Marco A.; Rocca, Paola; Rossi, Alessandro; Galderisi, Silvana (Frontiers in Psychiatry, 2024)
A considerable proportion of patients with schizophrenia perform below population norms on standardized neuropsychological tests, and the performance of those performing within normal range is lower than predicted based on parental education. Cognitive impairment predates the onset of psychosis, is observed during symptom remission and in non-affected first-degree relatives of patients.At the present time, cognitive deficits are regarded as key features of schizophrenia, important determinants of poor psychosocial outcome and targets for both pharmacological and nonpharmacological treatment strategies.A group of eight key opinion leaders reviewed and discussed latest advances in scientific research and current good clinical practices on assessment, management, and treatment of CIAS. In the present paper they summarize the current evidence, identify main gaps between current knowledge and mental health services clinical practice, and provide practical recommendations to reduce the gap.